Behavior of stratification phenomenon in flow of Maxwell nanomaterial with motile gyrotactic microorganisms in the presence of magnetic field. (October 2017) - Ijaz Khan, M.; Waqas, M.; Hayat, T.; Imran Khan, Muhammad; Alsaedi, A.
Highlights: Mixed convective flow of Maxwell nanomaterial containing motile gyrotactic microorganisms is addressed. Magnetohydrodynamics (MHD) and stratifications are present. Computations are made to obtain the solution expressions. Graphical abstract: Abstract: The ultimate purpose of present article is to investigate the heat, mass and motile microorganisms transfer rates in the convective stretched flow of Maxwell fluid consisting of nanoparticles and gyrotactic microorganisms. Magneto nanofluid in presence of mixed convection and stratification is considered. Concept of microorganisms is utilized just to stabilize the suspended nanoparticles through bioconvection which has been induced by combined effects of buoyancy forces and magnetic field. Further interesting aspects of Brownian motion, thermophoresis and stratification are examined. Convergent series solutions for the obtained nonlinear differential systems are derived. Impacts of different emerging parameters on velocity, temperature, concentration and motile microorganisms density are addressed through graphs. Numerical values for the local Nusselt, Sherwood and density number of motile microorganisms are computed and analyzed. It is observed that thermal, concentration and motile density stratification parameters result in the reduction of temperature, concentration and motile microorganisms density distributions, respectively.